Targeting O-GlcNAcylation to overcome resistance to anti-cancer therapies - Very, Ninon; El Yazidi-Belkoura, Ikram (Frontiers in Oncology, 2022)
In cancer cells, metabolic reprogramming is associated with an alteration of the O GlcNAcylation homeostasis. This post-translational modification (PTM) that attaches O GlcNAc moiety to intracellular proteins is dynamically and finely regulated by the O GlcNAc Transferase (OGT) and the O-GlcNAcase (OGA). It is now established that O GlcNAcylation participates in many features of cancer cells including a high rate of cell growth, invasion, and metastasis but little is known about its impact on the response to therapies. The purpose of this review is to highlight the role of O-GlcNAc protein modification in cancer resistance to therapies. We summarize the current knowledge about the crosstalk between O-GlcNAcylation and molecular mechanisms underlying tumor sensitivity/resistance to targeted therapies, chemotherapies, immunotherapy, and radiotherapy. We also discuss potential benefits and strategies of targeting O-GlcNAcylation to overcome cancer resistance.